2008
DOI: 10.1068/p5833
|View full text |Cite
|
Sign up to set email alerts
|

On Facial Expertise: Processing Strategies of Twins' Parents

Abstract: Parents of monozygotic twins typically learn to recognise their own children and also to tell them apart on photographs. However, it is unknown whether such exemplar expertise can be generalised to unfamiliar faces of equal similarity (ie other twins). In the present study, parents of monozygotic twins were compared to 'control' parents whose children were non-twin siblings. In a same/different task with familiar and unfamiliar twin faces as stimuli, twins' parents were faster than control parents in distingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Sensory systems need to effectively represent these stimuli according to perceptual categories, which are often defined through learning. For example, it has been shown that parents of identical twins learn to use subtle visual cues to discriminate between their own twin children, but the effect of this learning is highly specific and does not generalize to other twins (Sæther and Laeng, 2008). We consider the effect of learning on two factors related to the effectiveness of sensory representations.…”
Section: Introductionmentioning
confidence: 99%
“…Sensory systems need to effectively represent these stimuli according to perceptual categories, which are often defined through learning. For example, it has been shown that parents of identical twins learn to use subtle visual cues to discriminate between their own twin children, but the effect of this learning is highly specific and does not generalize to other twins (Sæther and Laeng, 2008). We consider the effect of learning on two factors related to the effectiveness of sensory representations.…”
Section: Introductionmentioning
confidence: 99%
“…While the ability to recognize oneself in a mirror is already generally developed at approximately age two [ 34 ], studies indicate that two-years old twins discriminate their own faces from the face of their co-twins only if exposed to the facial stimuli for a long period of time [ 35 ]. Recently, twins’ faces have been used as experimental visual stimuli [ 36 39 ], and twins have been employed as experimental subjects [ 39 42 ]. However, thus far no empirical evidence has been reported about the ability of adult twins to discriminate their own face from the face of his/her co-twin.…”
Section: Introductionmentioning
confidence: 99%
“…For example, although radiologists are experts at finding and detecting radiological anomalies they do not show a general advantage in visual search tasks such as "Where's Waldo" or the "NINA" drawings from The New York Times (Nodine and Krupinski, 1998 ). In another investigation, parents of monozygotic twins were faster at discriminating their own twins' faces, but this increased discrimination did not generalize to unfamiliar twin pairs (Saether and Laeng, 2008 ). However, other investigations have found at least partial generalization…”
Section: Generalization Of Perceptual Expertisementioning
confidence: 93%